Baseball tips - Hughes, Dean, 1943-; Hughes, Tom, 1968-; Lyall, Dennis (New York : Random House, 1993)
A beginner's guide to baseball basics with tips on how to hit, run bases, field, throw, and sharpen skills through practice
Includes index
Keywords: Baseball